Genetic insights on the relation of vascular risk factors and cervical artery dissection - Le Grand, Quentin; Ecker Ferreira, Leslie; Metso, Tiina M.; Schilling, Sabrina; Tatlisumak, Turgut; Grond-Ginsbach, Caspar; Engelter, Stefan T.; Lyrer, Philippe; Majersik, Jennifer J.; Worrall, Bradford B.; Southerland, Andrew M.; Markus, Hugh S.; et al. (Journal of the American College of Cardiology, 2023)
Background - The association between vascular risk factors and cervical artery dissections (CeADs), a leading cause of ischemic stroke (IS) in the young, remains controversial. - Objectives - This study aimed to explore the causal relation of vascular risk factors with CeAD risk and recurrence and compare it to their relation with non-CeAD IS. - Methods - This study used 2-sample Mendelian randomization analyses to explore the association of blood pressure (BP), lipid levels, type 2 diabetes, waist-to-hip ratio, smoking, and body mass index with CeAD and non-CeAD IS. To simulate effects of the most frequently used BP-lowering drugs, this study constructed genetic proxies and tested their association with CeAD and non-CeAD IS. In analyses among patients with CeAD, the investigators studied the association between weighted genetic risk scores of vascular risk factors and the risk of multiple or early recurrent dissections. - Results - Genetically determined higher systolic BP (OR: 1.51; 95% CI: 1.32-1.72) and diastolic BP (OR: 2.40; 95% CI: 1.92-3.00) increased the risk of CeAD (P < 0.0001). Genetically determined higher body mass index was inconsistently associated with a lower risk of CeAD. Genetic proxies for β-blocker effects were associated with a lower risk of CeAD (OR: 0.65; 95% CI: 0.50-0.85), whereas calcium-channel blockers were associated with a lower risk of non-CeAD IS (OR: 0.75; 95% CI: 0.63-0.90). Weighted genetic risk scores for systolic BP and diastolic BP were associated with an increased risk of multiple or early recurrent CeAD. - Conclusions - These results are supportive of a causal association between higher BP and increased CeAD risk and recurrence and provide genetic evidence for lower CeAD risk under β-blockers. This may inform secondary prevention strategies and trial design for CeAD.
Gesehen am 19.03.2024